PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI SATUAN POLISI PAMONG PRAJA KECAMATAN SENEN - Rismayanda Simbolon; Hery Wihasnanto (Jurnal Manajemen Bisnis Krisnadwipayana, 2021)
To determine the Effect of Motivation and Work Environment on Employee Performance of Satuan Polisi Pamong Praja Kecamatan Senen. The method used is a descriptive method with an associative approach. The sampling technique used is non-probability sampling using a saturated sampling technique method with a sample of 85 Satpol PP Kecamatan Senen. Data analysis used simultaneously and partially linear regression analysis. The results showed that motivation and work environment have an influence either partially or simultaneously on the performance of Satuan Polisi Pamong Praja Kecamatan Senen.